Increased ileal bile acid binding protein and galectin-9 are associated with mild cognitive impairment and Alzheimer's disease. (December 2019) - Wang, Xin; Niu, Ye; Yue, Chen-xi; Fu, Shuang; Wang, Rui-tao
Abstract: Enterocyte damage and subsequent microbial translocation drive neuroinflammation in the pathogenesis of Alzheimer's disease (AD). Human ileal bile acid binding protein (I-BABP) and intestinal fatty acid binding proteins (I-FABP) are the indicators of enterocyte damage. Lipopolysaccharide-binding protein (LBP) is an indirect marker of microbial translocation. The activation of peripheral innate immune cells plays a crucial role in modulating AD progression. Galectin-9 is a versatile immunomodulatory molecule. The purpose of this study was to determine I-FABP, I-BABP, LBP, and galectin-9 levels in MCI and AD and investigate the relationship between I-FABP, I-BABP, LBP and galectin-9. In this study, I-FABP, I-BABP, LBP, and galectin-9 levels were measured using ELISA assay in 115 AD patients, 115 MCI patients, and 115 non-demented control subjects. Increased I-BABP and galectin-9 were observed in MCI and AD patients. Furthermore, AD patients had higher I-BABP and galectin-9 levels compared with MCI patients. However, I-FABP and LBP in three groups had no difference. I-BABP levels were positively correlated with galectin-9, after adjusting confounding factors (r = 0.409, p < 0.001). In addition, multivariate analysis revealed that increased I-BABP and galectin-9 levels were significantly associated with reduced mini-mental state examination (MMSE) score. In conclusion, galectin-9 is correlated with I-BABP after adjusting confounding covariates. Moreover, increased I-BABP and galectin-9 in MCI and AD are significant factors for reduced MMSE score. Further studies are needed.